2020
DOI: 10.1055/a-1112-7096
|View full text |Cite
|
Sign up to set email alerts
|

Hindbrain Herniation and Banana and Lemon Sign After Open Fetal Myelomeningocele Repair – When Do These Signs Disappear and is Shunting Predictable?

Abstract: Purpose The aim was to describe the sonographic follow-up of hindbrain herniation (HH), the banana and lemon sign after fetal myelomeningocele (fMMC) repair, and the time of disappearance of these signs after the intervention, and to investigate any predictive value for the necessity of shunting during the infant’s first year of life. Additionally, the sonographic evolution of the transcerebellar diameter (TCD) before and after fetal intervention was assessed. Patients and Methods The first 50 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…However, all fetuses showed complete resolution of vasoconstrictive signs in MCA Doppler waveforms over time. Despite de-tethering of the spinal cord during fSB repair and its immediate cranial migration, decompression and expansion of the anatomical structures in the posterior fossa will take some time [28]. The gradual resolution of the constrictive MCA Doppler waveforms, from M-sign over a systolic shoulder to normal systolic downslope reflects the postoperative recovery process and coincides with the time of disappearance of the HH and its effect on the brain stem, which would support our previous hypothesis.…”
Section: Postoperative Observationssupporting
confidence: 84%
“…However, all fetuses showed complete resolution of vasoconstrictive signs in MCA Doppler waveforms over time. Despite de-tethering of the spinal cord during fSB repair and its immediate cranial migration, decompression and expansion of the anatomical structures in the posterior fossa will take some time [28]. The gradual resolution of the constrictive MCA Doppler waveforms, from M-sign over a systolic shoulder to normal systolic downslope reflects the postoperative recovery process and coincides with the time of disappearance of the HH and its effect on the brain stem, which would support our previous hypothesis.…”
Section: Postoperative Observationssupporting
confidence: 84%
“…The authors documented that the time lapse between fetal surgery and the disappearance of the 'banana' sign was not associated with the need for PCD surgery. 26 However, in our study, we used the size of the cerebellum as an indicator and found that the preoperative and postoperative TCD were acceptable and excellent predictors for PCD surgery, respectively.…”
Section: Principal Findingsmentioning
confidence: 78%
“…The abnormal configuration of the cerebellum is believed to stem from hindbrain herniation owing to a small posterior fossa in OSB fetuses 23 . Studies showed that after fetal surgery for OSB, the ‘banana’ configuration of the cerebellum disappeared in the majority of cases within the first month after the surgery; however, its size remained small in more than half of the cases 24–26 . A previous study explored the usage of TCD in predicting PCD surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra‐operative data included skin‐to‐skin operative time, length of the hysterotomy, dimensions of the lesion, neurosurgical operative time, whether the placode underwent tubularisation, and/or the dura were closed, or a skin substitute was used. Postoperative outcome measurements included reversal of hindbrain herniation within the first week, which according to experimental studies was an indicator of watertight closure of the defect, and in some studies correlated to a lower risk for shunt insertion, hence serving as a proxy for neuroprotection 5,14,15 Reversal was defined as reporting the re‐appearance of fluid around the cerebellum and brain, and partly or complete ascent of hindbrain. In the hysterotomy group this was as evidenced by MRI, and in the mini‐hysterotomy group the imaging modality was ultrasound.…”
Section: Methodsmentioning
confidence: 99%